2016
DOI: 10.1186/s12944-016-0301-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparing effects of soybean oil- and palm olein-based mayonnaise consumption on the plasma lipid and lipoprotein profiles in human subjects: a double-blind randomized controlled trial with cross-over design

Abstract: BackgroundMayonnaise is used widely in contemporary human diet with widespread use as a salad dressing or spread on breads. Vegetable oils used in its formulation may be a rich source of ω-6 PUFAs and the higher-PUFA content of mayonnaise may be beneficial in mediating a hypocholesterolemic effect. This study, therefore, evaluated the functionality of mayonnaise on cardiometabolic risk within a regular human consumption scenario.MethodsSubjects underwent a randomized double-blind crossover trial, consuming die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 49 publications
2
17
0
3
Order By: Relevance
“…Supplementation of the two types of oils (SO and BNO) did not significantly change the glucose levels, which is consistent with previous studies [42,58,59].…”
Section: Discussionsupporting
confidence: 92%
“…Supplementation of the two types of oils (SO and BNO) did not significantly change the glucose levels, which is consistent with previous studies [42,58,59].…”
Section: Discussionsupporting
confidence: 92%
“…Salad dressings often contain around 40% of fat, and a considerable amount of high fructose corn syrup, which has been proven to increase lipid synthesis and is associated with dyslipidemia [ 47 ]. Furthermore, mayonnaise is a major ingredient as a salad dressing alone or as part of other popular dressings (e.g., thousand islands), and studies have found that the use of palm oil, a cheaper oil comparatively, in its preparation caused an increase in total and LDL-C compared to the use of soybean oil, which is a more expensive type [ 48 ]. Therefore, the consumption of dressing can distort potential beneficial influences of vegetable consumption on serum lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies are included in this review [3138]. Comparisons were made in between palm oil or palm olein with partially hydrogenated soybean oil (PHSO) [31,32], soybean oil [31,33] and olive oil [34,38], with two studies in each of the comparison. Comparisons of palm oil consumption with other vegetable oils could not be made for 2-hour post prandial glucose and HbA1C (no studies) in view of limited available evidence (one study) [35].…”
Section: Resultsmentioning
confidence: 99%